2022
DOI: 10.4103/0028-3886.359176
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Schwannomatosis of the Lower Extremity – A Case Series

Abstract: Segmental schwannomatosis involving a nerve in single limb is uncommon. Schwannomatosis is used to describe a distinct clinicopathological disease of multiple schwannomas without manifestations of neurofibromatosis, and it is termed segmental when a single extremity is involved. Surgery is indicated when there is progressive clinical deterioration or progressive increase in size of the tumors. We present a case series of segmental schwannomatosis involving the lower limb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Von Deimling et al, 14 reported a 46 year old male who had 18 separate lesions along the medial plantar division of the posterior tibial nerve who had a history of pain in his foot for 18 months prior to the diagnosis and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Von Deimling et al, 14 reported a 46 year old male who had 18 separate lesions along the medial plantar division of the posterior tibial nerve who had a history of pain in his foot for 18 months prior to the diagnosis and surgery.…”
Section: Discussionmentioning
confidence: 99%